The impact of left-behind experience on the mental health and marital satisfaction - Zheng, Jichao; Yan, Lei (Frontiers in Psychology, 2025)
BackgroundChina has a large number of people who migrate internally to work outside their hometown, and at the same time, tens of millions of left-behind spouses stay home alone to take care of their families, so it is important to study the psychological health and marital satisfaction of left-behind spouses.MethodWe used the China Family Panel Studies (CFPS) data 2022 and 2020, which included 8,096 married respondents, 437 of whom have left-behind experiences. Linear regression was used to examine the relationship among left-behind experience, depressive symptoms, and marital satisfaction. We also ran regressions on male and female samples and urban and rural samples to find the heterogeneous effects of the experience of staying behind.ResultsShort-term and previous left-behind experiences had no significant effect on the mental health of the left-behind spouses. Only long-term left-behind experience had a significant negative impact, resulting in an increase in the depression value by 1.16. Long-term left-behind experience also negatively affected the marital satisfaction of the left-behind spouses, decreasing the marital satisfaction value by 0.26.ConclusionLong-term left-behind experience is detrimental to the psychological health and marital satisfaction of the spouses left behind, and efforts should be made to reduce the separation of couples due to going out to work and to promote local employment. At the same time, rural left-behind women are a special vulnerable group, and efforts should be made to improve their mental health and provide them with more social support and psychological intervention.